Human Computer Confluence. Transforming Human Experience Through Symbiotic Technologies - Viaud-Delmon, Isabelle (De Gruyter, 2016)
Human-computer confluence refers to an invisible, implicit, embodied or even implanted interaction between humans and system components. New classes of user interfaces are emerging that make use of several sensors and are able to adapt their physical properties to the current situational context of users. A key aspect of human-computer confluence is its potential for transforming human experience in the sense of bending, breaking and blending the barriers between the real, the virtual and the augmented, to allow users to experience their body and their world in new ways. Research on Presence, Embodiment and Brain-Computer Interface is already exploring these boundaries and asking questions such as: Can we seamlessly move between the virtual and the real? Can we assimilate fundamentally new senses through confluence? The aim of this book is to explore the boundaries and intersections of the multidisciplinary field of HCC and discuss its potential applications in different domains, including healthcare, education, training and even arts.